Effect of canopy positions on physicochemical quality of Mandarin Fruit cv. 'Shogun' during Storages - Youryon, P.; Supapvanich, S. (My University, 2019)
The effect of canopy positions (upper, middle and lower) on quality of mandarin fruit cv. 'Shogun' stored at 20°C and 10°Cwas investigated. The results showed that the canopy positions influenced the appearance and peel colour which the peel of fruits from the upper part had more yellow and chroma value than the fruits from middle and lower parts which the peel had more green colour. The canopy positions had no influenced on the fruit pulp colour. The fruits from the upper part had total soluble solids (TSS), antioxidant activity (AA), ascorbic acid (AsA), total phenols (TP) and total flavonoids (TF) contents higher than the fruits from middle and the lower parts whilst total acidity (TA) of the fruits from different canopy positions was similar. During storage, most physicochemical quality attributes seemed constant, except TA which decreased on day 7 and antioxidant activity of the fruits stored at 10 °C which decreased on day 21. In conclusion, the canopy positions had influenced on 'Shogun' mandarin fruit quality which the fruits from the upper part had quality higher than the fruits from middle and lower parts.
Keywords: Bioactive compounds; Canopy positions; Mandarin fruit; Postharvest quality